Vessel-Associated Immune Cells in Cerebrovascular Diseases: From Perivascular Macrophages to Vessel-Associated Microglia - Koizumi, Takashi; Kerkhofs, Danielle; Mizuno, Toshiki; Steinbusch, Harry W. M.; Foulquier, Sébastien (Frontiers in Neuroscience, 2019)
Cerebral small vessels feed and protect the brain parenchyma thanks to the unique features of the blood brain-barrier. Cerebrovascular dysfunction is therefore seen as a detrimental factor for the initiation of several CNS disorders, such as stroke, cerebral small vessel disease and Alzheimer’s disease. The main working hypothesis linking cerebrovascular dysfunction to brain disorders includes the contribution of neuroinflammation. While our knowledge on microglia cells – the brain-resident immune cells - has been increasing the last decades, the specific populations of microglia and macrophages surrounding brain vessels, vessel-associated microglia and perivascular macrophages respectively, have been overlooked. This review aims to summarize the knowledge gathered on vessel-associated microglia and perivascular macrophages, to discuss existing knowledge gaps of importance for later studies and to summarize evidences for their contribution to cerebrovascular dysfunction.